A Step-by-Step Dissection of Cerebral Pathologies for Neurosurgical Trainees: The Middle Cerebral Artery Bifurcation Aneurysm - Sannwald, Lennart Wilhelm; Moskopp, Mats Leif; Moskopp, Dag (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Aneurysmal subarachnoid hemorrhage remains one of the most prevalent causes of strokes in the young causing a high socioeconomic damage. Both emergent and elective treatments of intracranial aneurysms remain essential challenges for neurovascular centers. We aim to present conceptual education on clip ligation of middle cerebral artery bifurcation aneurysms in an accessible and structured way to maximize the educational takeaway of residents from aneurysm cases.Methods After 30 years of experience of the senior author in cerebrovascular surgery in three centers, we closely reviewed an exemplary case of elective right middle cerebral artery bifurcation aneurysm clipping and contrasted it to an alternative microneurosurgical approach to illustrate key principles of microneurosurgical clip ligation for neurosurgical trainees.Results Dissection of the sylvian fissure, subfrontal approach to the optic-carotid complex, proximal control, aneurysm dissection, dissection of kissing branches, dissection of aneurysm fundus, temporary and permanent clipping, as well as aneurysm inspection and resection are highlighted as key steps of clip ligation. This proximal-to-distal approach is contrasted to the distal-to-proximal approach. Additionally, general principles of intracranial surgery such as use of retraction, arachnoid dissection, and draining of cerebrospinal fluid are addressed.Conclusion Due to a constantly decreasing case load in the era of neurointerventionalism, the paradox of facing increased complexity with decreased experience must be met with a sophisticated practical and theoretical education of neurosurgical trainees early on and with a low threshold.
Keywords: vascular neurosurgery; aneurysm; educational